Analysis of Coupling Coordination Degree of Digital Economy Industry Synergistic Development—Empirical Evidence Based on Urban Agglomerations in the Northern Region of China - Wang, Ling; Liu, Renwei (International Journal of Global Economics and Management, 2024)
With the rise of the national strategic position of Beijing-Tianjin-Hebei city cluster, Central Plains city cluster and Shandong Peninsula city cluster, inter-city cluster collaboration has become particularly important, and scientific evaluation of the level of digital economy industry synergistic development of major northern city clusters is conducive to cracking the dilemma of industrial synergy of major northern city clusters, and forming the pattern of high-quality integrated development. The data related to digital infrastructure, digital industrialization and industrial digitization of the Beijing-Tianjin-Hebei city cluster, the Central Plains city cluster and the Shandong Peninsula city cluster from 2013 to 2021 are selected, and the coupled synergy model is applied to evaluate the level of collaborative development of digital economy industries in major northern city clusters based on the analysis of digital economy industry development in major northern city clusters. The study found that: the coupling and coordination degree of digital economy industry of the three major northern city clusters from 2013 to 2021 has been improving, and the digital economy industry of the Beijing-Tianjin-Hebei city cluster will reach the intermediate level of coordination in 2021; in terms of the spatial synergy of the digital economy industry of the three city clusters, the synergy of the digital economy industry among the three clusters has reached the level of just barely dislocation, but the degree of industrial digitization synergy among the three clusters has obviously lags behind the level of digital infrastructure synergy and industrial digitalization synergy. Based on this, it puts forward countermeasures and suggestions to accelerate the top-level design of digital economy industry synergistic development in the major northern city clusters and to establish institutional mechanisms to support the synergistic development of digital economy industry in the cities.